Strategy of Population Data Transfer Services through the Online Population Service System (SILOKA) - Radityo Dimas Prabowo; Nurliah Nurdin (Yayasan Riset dan Pengembangan Intelektual, 2025)
This research is motivated by the problem of the suboptimal implementation of population data transfer services through SILOKA in Bogor Regency. The problem formulation in this study is why the population data transfer service through SILOKA has not been optimal, and how the strategy to optimize it. This research is based on the E-Government theory by Heeks and Bailur which includes the dimensions of service process speed, accessibility, procedural transparency, and service attitude. This research uses a descriptive qualitative method with data collection techniques through interviews, observations, and documentation. The results show that the implementation of population data transfer services through SILOKA in Bogor Regency still experiences three obstacles: First, there are SILOKA websites that are no longer functioning. Second, there is no specific website that is fast and of good quality for SILOKA services. Third, there is no SILOKA application available on the Playstore and App Store. The strategies to improve the quality of population data transfer services through SILOKA include: First, deleting failed websites that are no longer functioning. Second, creating a specific, fast, and high-quality website for SILOKA. Third, developing a SILOKA application that can be downloaded through the Playstore and App Store with user-friendly features, so that it can be easily accessed by Android and iOS users.